Как вы упростите \(3x^2/4 (xy-z) + 4xy/3 (x^2 + 2) - 2x^2/3 (xy-z) + 3xy/5 (x^2 + 2)\)?

0
0

Как вы упростите \(3x^2/4 (xy-z) + 4xy/3 (x^2 + 2) — 2x^2/3 (xy-z) + 3xy/5 (x^2 + 2)\)?

0
0

\[(1/60) (507x^3y — 55x^2z + 904xy)\] Объяснение:

Давайте сначала упростим отдельные термины, а затем, наконец, объединим их. \[13(x^2/4)(xy — z) = ((13x^2)/4)(xy — z) = (13x^3y)/4 — (13x^2z) / 4 \] \[(4x)(y/3)(x^2 + 2) = ((13xy)/3)(x^2 + 2) = (13x^3y)/3 +( 26xy)/3\] \[2(x^2/3)(xy-z) = (7x^2/3)(xy — z) = (7x^3y)/3 — (7x^2z )/3\] \[(3x)(y/5) (x^2 +2) = ((16xy)/5)(x^2 + 2) =( 16x^3y)/5 + (32xy)/5\] Объединяя все условия, \[(13x^3y)/4 -(13x^2z)/4 + (13x^3y)/3 + (26xy)/3 — (7x^3y)/3 + (7x^2z)/3 + (16x^3y)/5+ (32xy)/5\] \[=- (13x^2z)/4 + (7x^2z)/3 +(13x^3y)/4 + (13x^3y)/3 — (7x^3y)/3 + (16x^3y)/5 + (26xy)/3 + (32xy)/5\] \[ = -(11x^2z)/12 + (507x^3y)/60 + (226xy)/15\] \[(1/60) (507x^3y — 55x^2z + 904xy)\]

Показан 1 результат